A Study on Entrapment Efficiency of Earthworms (Lumbricus rubellus) Extract in the Ethosomal Drug Delivery System - Pratiwi, Sabrina Resky; Ainiah, Nur; Hardyanti, Hardyanti; Putri, Dini Rusdayanti; Utomo, Emilia (Hasanuddin University, 2017)
IntroductionEarthworms (Lumbricus rubellus) extract is known to contain bioactive protein as antibacterial compounds. One of the disadvantages of polar compounds is slow penetration into the skin layers which can be solved by formulating it in the form of ethosomal drug delivery system. The aims of this research was to get information about ethanol concentration that can give the highest entrapment efficiency of the ethosome. MethodsEarthworms powder was macerated using 50% ethanol for 3 days. The extract was formulated into ethosome with variation of ethanol concentration that are 20%, 30%, 40%, and 50%, respectively. The measurement of entrapment efficiency was conducted by measuring the amount of active protein of earthworms extract that was entrapped in ethosome vesicles using spectrophotometer UV-Visible.ResultsThe results showed that the highest entrapment efficiency was 72.58 % performed by formula which was made with 0.5 % extract, 2 % soy lecithin and 50 % ethanol.ConclusionsThe highest percentage of entrapment efficiency of earthworms extract ethosome was 72.58%.Keywords : ethosome, ethanol concentration , entrapment efficiency, Lumbricus rubellus.